Behçet Disease-Like Symptoms with a Novel COPA Mutation. (11th January 2020) - Anderson, E.; Hatch, J.; Cardinal, J.; Langguth, D.; Coman, D.
Abstract : COPA syndrome is a recently described autosomal dominant disorder with key immune dysregulation caused by defects within the COPA gene. These mutations lead to endoplasmic reticulum stress and autoimmune response with upregulation of Th17 cytokines. The clinical phenotype of COPA syndrome primarily comprised pulmonary disease, arthritis, and renal disease secondary to immune dysregulation, with onset of symptoms commonly in the first decade of life. Herein, we describe a family with an attenuated Behçet-like phenotype of COPA syndrome, further expanding the phenotypic understanding of this syndrome.